Two new species of Olpium L. Koch, 1873 from Iran, with an identification key to all species of the genus (Pseudoscorpiones: Olpiidae) - Latifi, Zahra; Mirshamsi, Omid; Aliabadian, Mansour; Harms, Danilo; Novák, János (Zootaxa, 2026)
Despite its broad distribution across arid and semi-arid regions of Africa, Asia, southern Europe, and Australia, the pseudoscorpion genus Olpium L. Koch, 1873 (Pseudoscorpiones: Olpiidae) remains taxonomically neglected in Iran and only two species (O. omanense Mahnert, 1991 and O. lindbergi Beier, 1959) have been recorded from this country to date. Following detailed morphological study of extensive field collections in Iran, we describe two new species, O. tenebris sp. nov. and O. lacustre sp. nov., that are widely distributed across the country. Comprehensive descriptions, illustrations, and comparisons with closely related species are provided. To facilitate standardized identification and character evaluation, we present an updated species-level key for the genus Olpium, constructed using DELTA software.